UJI ANTIBAKTERI EKSTRAK KOMBINASI DAUN PEGAGAN (CENTELLA ASIATICA) DAN SURUHAN (PEPEROMIA PELLUCIDA L. KUNTH) TERHADAP BAKTERI PROPIONIBACTERIUM ACNES - Habibah, Nur; Aprilia, Indri Ayu; Dhyanaputri, I Gusti Ayu Sri (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2024)
Propionibacterium acnes is one of the normal skin flora that can cause acne. Acne treatments can be done by utilizing natural ingredients. Pegagan and suruhan leaves contain flavonoids, alkaloids, saponins, tannins, and triterpenoids that have antibacterial activity. This study aims to determine the antibacterial activity of the combined extract of pegagan and suruhan leaves against Propionibacterium acnes. This research is a pre-experimental research with a shot case study design using the Kirby-Bauer disc diffusion method. There were four concentrations of the combined extracts that were tested, there were 20, 40, 60, and 80%, as well as 30 µg chloramphenicol and 96% ethanol as positive and negative controls. The results showed that the combined extracts of pegagan and suruhan leaves were able to inhibit the growth of Propionibacterium acnes with the inhibition zone diameters of 4.41; 6.91; 7.25; and 7.91 mm at concentrations of 20, 40, 60, and 80%, respectively. The zone of inhibition of Propionibacterium acnes growth was proportional to the concentration of the combination extracts. Kolmogorov Smirnov test showed a value of ρ>α (0.05) which proved that the data was normally distributed. One Way Anova test showed the value of ρ<α (0.05) which proves that there are differences in the inhibition zone at various concentrations. Based on these results, it can be concluded that the combined extract of pegagan and suruhan leaves has antibacterial activity against the growth of Propionibacterium acnes.